Dasar-Dasar dan Tujuan Pemikiran Pendidikan Islam - Abadi Sf, Andi Nurjaya (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Islamic Educational Philosophy Development: An Integration of Reason and Revelation (Wahey) aligned with Islamic Faith It takes its basis from Qur'an, Hadith and opinions of Islamic scholars, emphasizing the primary significance for quest of strength, for nay believe and for arête. Islamic learning also implanted by a values of Tawhid that Allah as a final goal in the process of the learning. Islamic education is systematically based on the Qur'an, As-Sunnah, Islamic Philosophy, psychology, sociology, and axiology. Islamic education aims to produce men who are balanced spiritually, intellectually, and emotionally, and who will contribute positively to society. Islamic educative thought pursue to develop scientific and critical thought, produce knowledge, and nurture a spirit of ijtihad. On the whole, the objective of Islamic education is to develop an educated, faith-based, ethics person and the creative role of Khalifah on earth to achieved happiness in the world and the last.